Etude de l'appareil radical de jeunes plants de Chênes verts dont le pivot se développe sans amputation, ni déviation - BEISSALAH, Y; AMIN, T; EL HAJZEIN, B; NEVILLE, P; BERNARD, Janine (Ann. For. Sci., 1988)
The experimental study of the root system of woody plants is far behind that of the aerial system. To make up for this difference, a study was begun on a Mediterranean sclerophyllous oak (Quercus ilex L.). The present study defines the developmental characteristics of the root system in young seedling whose tap root has neither been diverted nor amputated and which grows in different ecological conditions (substrates, temperatures). The results obtained can be used as an interpretative guide for the root system’s reactions to both diverting and amputating. These reactions will be described elsewhere. The study was made in R IEDACKER type minirhirotrons (1974) and L AMOND type fog chambers (1975). The root system of holly oak seedlings (fig. 1) consists of one main root (tap root) with positive geotropism and rapid and theoretically unlimited growth, from which thin, usually short, branch roots, either subhorizontal or oblique with slow, limited growth, spread out (fig. 5). The tap root is not rectilinear, but ondulates more or less regulary (fig. 1), both in loosely-packed substrates (peat ou loam) and in the absence of any substrate (fog chamber). The substrate’s resistance to root penetration, therefore, does not cause these ondulations. The largest branch roots generally begin growth on the convex part of the ondulation (fig. 1, B and C). The tap root grows better in peat than in loam or fog chambers (fig. 2). Its growth is subject to different types of fluctuations (fig. 4). It is highly sensitive to thermic variations (fig. 2 and 3). A 5 °C temperature drop (from 25 °C to 20 °C) decreases its growth rate by a quarter in peat and by half in loam (fig. 2). This decrease is lower in fog chambers because of their neutralizing effect. The tap root’s growth rate also fluctuates regardless of temperature, substrate (peat or loam), or lack of substrate (fig. 4). The fluctuation period varies from 2 to 7 days and is probably the expression of an irregular endogenetic rythm. Systematic ablation of branch roots as they appear has not effect on the variations in the tap root’s growth rate. Anatomy also differentiates the tap root from branch roots. The tap root usually has 6 major xylem fascicles (more rarely 4 to 8) directly underneath the cotyledons and connected to them in groups of three per cotyledon (fig. 6). Between these are often extra xylem fascicles which are smaller, connected to the epicotyle and disappear rapidly lower down (fig. 7, A and A’). The major xylem fascicles divide between the 3‘d and T&dquo; centimeter from the cotyledon by enlarging and isolating their wings (fig. 7, A and B) which can result at most in a tripling of the number of xylcm fascicles. These additional fascicles vanish progressively either by fusion and/or reduction up to the 20’&dquo; centimeter from the cotyledon (fig. 7, C). Beyond this, we find the same number of xylem fascicles as at the start, i.e. only major fascicles remain (fig. 7, D). The number of phloem fascicles, at first twice that of the major xylem fascicles in the area of the tap root near the cotyledons (fig. 7, A and B), decreases progressively, generally by fusion, until it equals the latter beyond the 20’&dquo; centimeter from the cotyledon (fig. 7, D). This remarkable fluctuation in fascicle number is probably related to the period of cotyledon influence. It is not present in the branch roots, which have between 3 and 5 xylem fascicles alternating with an equal number of phloem fascicles.
Keywords: development; Quercus ilex; rool; Seedling; Temperature; vascular bundles